2020
DOI: 10.1021/acsami.0c08926
|View full text |Cite
|
Sign up to set email alerts
|

Printable 3D Carbon Nanofiber Networks with Embedded Metal Nanocatalysts

Abstract: Carbon nanofiber (CNF)-nanocatalyst hybrids hold great promise in fields such as energy storage, synthetic chemistry and sensors. Current strategies to generate such hybrids are laborious and utterly incompatible with miniaturization and large-scale production. Instead, this

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 52 publications
4
18
0
Order By: Relevance
“…In addition, Liu et al reported linear range of 1 to 800 µM with a low detection limit of 0.6 µM for a H 2 O 2 electrochemical sensor for an electrode loaded by Pt nanoparticles and CNFs [ 337 ]. A sensitivity down to 1 nM and high selectivity for glucose molecules was presented by Kim et al, using cobalt-oxide-incorporated multichannel carbon nanotubes [ 338 ], while Simsek et al reached a detection limit of 0.3 µM glucose with Ni nanoparticles adhered to a CNF network [ 339 ].…”
Section: Sensorsmentioning
confidence: 99%
“…In addition, Liu et al reported linear range of 1 to 800 µM with a low detection limit of 0.6 µM for a H 2 O 2 electrochemical sensor for an electrode loaded by Pt nanoparticles and CNFs [ 337 ]. A sensitivity down to 1 nM and high selectivity for glucose molecules was presented by Kim et al, using cobalt-oxide-incorporated multichannel carbon nanotubes [ 338 ], while Simsek et al reached a detection limit of 0.3 µM glucose with Ni nanoparticles adhered to a CNF network [ 339 ].…”
Section: Sensorsmentioning
confidence: 99%
“…4a) is a promising strategy to overcome such challenges. Our research group has recently demonstrated the feasibility of the technique in generating high-performance non-enzymatic electrochemical transducers under ambient conditions [88,89]. We initially investigated fabrication parameters that critically govern the morphology and electrochemical properties of the laserinduced carbon nanofibers (LCNFs) [88].…”
Section: Laser-induced Carbon Nanofibersmentioning
confidence: 99%
“…b SEM images show the side view of LIG, electrospun nanofibers before (ii) and after laser carbonization (iii), electrocatalytic activity of LCNFs containing Fe in comparison to screen-printed carbon (SPCE) and gold (SPGE) electrodes (iv and v) [88]. c TEM images from low-to high-magnification display the presence of Ni nanoparticles in LCNFs after laser writing (i-iii), stacked graphene sheets present within LCNFs (iv), morphological structure of as-spun nanofibers containinh Ni before (v) and after (vi), and distribution of Ni on LCNF electrode studied by EDS (viii) [89]. d Amperograms of glucose at various LCNF electrodes (i), and calibration plot of glucose obtained from LCNFs with 25% Ni (ii) [89].…”
Section: Advances In Laser-induced (Functional) Carbon Nanomaterials In Sensing Applicationsmentioning
confidence: 99%
See 2 more Smart Citations